The Risks of Innovation : Are Innovating Firms Less Likely to Die? - Fernandes, Ana M.; Paunov, Caroline (World Bank, Washington, DC, 2012)
While innovation is a source of competitiveness, it may expose plants to survival risks. Using a rich set of plant-product data for Chilean manufacturing plants during the period 1996-2006 and discrete-time hazard models controlling for unobserved plant heterogeneity, this paper shows that innovating plants have higher survival odds. However, risk plays an important role for the innovation-survival link: only innovators that retain diversified sources of revenues survive longer. Single-product innovators are at greater risk of exiting. In addition, only innovators facing lower market risk, measured by fewer innovative competitors, low-pricing strategies, or lower sales volatility in the new products' markets, see their odds of survival increase significantly. Technical risk, measured by the proximity of product innovations to the plants' past expertise, the degree of sophistication of new products, or their novelty to the Chilean market, does not play a substantial role in the innovation-survival link. Engaging in risky innovation is not an irrational decision, since plants reap big payoffs -- higher productivity, employment and sales growth -- from such innovations. However, those payoffs are not always higher than those from cautious innovation, suggesting that constraining factors, such as credit constraints, force plants to take on more risk when innovating. An implication of the findings for industry dynamics is that among innovators, only the survival of cautious innovators is guaranteed. Since engaging in cautious innovation may not be feasible for all plants, there could be a role for policy in reducing innovators' exposure to risks and providing assistance to deal with failed innovations, while setting the right incentives.